Using Alternative Assessment to Assess Undergraduate EFL Students at Yemeni Universities: Challenges from the Perspectives of Faculty - Marwan Saeed Saif Moqbel (Hasanuddin University, 2020)
The present study aimed at investigating alternative assessment (AA) within the Yemeni university EFL classrooms in terms of identifying the challenges of using AA to assess undergraduate EFL students from the perspectives of the faculty. Data were collected, through a questionnaire, from (66) lecturers and professors of different ranks who teach EFL at the collegiate level in two Yemeni public universities and one national university. The results of the study indicated that faculty members of English departments at Yemeni universities face some challenges of using AA to assess undergraduate EFL students. These challenges belong to various factors, including the instructional environment, the students, the management of Yemeni universities, the faculty members, or the nature of AA. Statistically significant differences were found in the mean scores according to years of experience variable between respondents with less than 5 years and those with 5-10 years of experience in favor of those with less than 5 years of experience, but not according to the type of university, gender, and specialization variables. Accordingly, some recommendations were given to address the identified challenges, which might lead to a better implementation of AA in Yemeni university EFL classrooms.